Increasing Trend Of Tb Cases 2021-2023 In Urban Areas: Correlation Study Of Population Density With Number Of Tb Cases - Yulis Indriyani; Teguh Irawan; Chelsy Rachel Dwindasari; Anis Tiara Sari Wihar; Luthfiyatul Karimah; Salsabilla Dwi Ramadhani (PT. Anagata Sembagi Education, 2024)
Tuberculosis or TB is a type of infectious disease that is the center of world attention because it spreads very quickly and causes death. According to data from the Pekalongan Health Service, TB cases increase every year, in 2021 there were 347 cases, in 2022 there were 459 cases and in 2023 there were 505 cases. The research aims to determine the profile of TB cases, their characteristics based on age and gender and analyze the relationship between population density and the number of TB cases in Pekalongan Urban Area. The research design is an observational study on secondary data on the number of TB cases in 2021-2023 in Pekalongan Urban Areas. Using purposive sampling, the total research sample focused on four areas, namely North Pekalongan District, South Pekalongan District, East Pekalongan District and West Pekalongan District. Data collection techniques are observation and literature study. Descriptive data analysis and inferential analysis uses the Pearson Correlation Test. The research results explain that almost every sub-district in Pekalongan Urban Areas during 2021-2023 experienced an increasing trend in the number of TB cases. Based on age, the highest trend of TB cases occurs in productive age (15-65 years) compared to children. Based on gender, the highest number of TB cases occurs in men. On the other hand, no relationship was found between population density and the number of TB cases in Pekalongan Urban Areas (p value = 0.380 > 0.05). So, integrated preventive and promotive efforts are needed from the community.